Extracorporeal Pedicles for Free Flap Reconstruction in Diabetic Lower Extremity Wounds - Gimenez, Alejandro R.; Lazo, Daniel; Chade, Salomao; Fioravanti, Alex; Colicchio, Olimpio; Alvarez, Daniel; Junior, Ernani; Raj, Sarth; Abu-Ghname, Amjed; Maricevich, Marco (Archives of Plastic Surgery, 2022)
Diabetic foot ulcers are a severe complication of diabetes, and their management requires a multidisciplinary approach for optimal management. When treating these ulcers, limb salvage remains the ultimate goal. In this article, we present the “hanging” free flap for the reconstruction of chronic lower extremity diabetic ulcers. This two-staged approach involves standard free flap harvest and inset; however, following inset the “hanging” pedicle is covered within a skin graft instead of making extraneous incisions within the undisturbed soft tissues or tunnels that can compress the vessels. After incorporation, a second-stage surgery is performed in 4 to 6 weeks which entails pedicle division, flap inset revision, and end-to-end reconstruction of the recipient vessel. Besides decreasing the number of incisions on diabetic patients, our novel technique utilizing the “hanging” pedicle simplifies flap monitoring and inset and allows reconstruction of recipient vessels to reestablish distal blood flow.
Keywords: diabetic foot ulcers; hanging pedicle; microvascular reconstruction; free tissue transfer